Differential Response of Carnation Varieties (Dianthus caryophyllus L.) to Different Levels of Boron under Polytunnels - Dahal, Januka; Adhikari, Debraj; Kumar Pun, Umed (International Journal of Environment, 2020)
Carnation (Dianthus caryophyllus L.) is one of the most commercially important cut flowers of the world. It can be used for cut flowers, bedding, edging, boarders, pots and rock garden. Four Spanish carnation varieties were tested with three levels of boron under ultra-violet stabilized polytunnels from August 2017 to April 2018 at Godawari, Nepal. The objective of the research was to evaluate vegetative, floral, and vase life parameters in relations to growth, yield and quality of carnation. The research was conducted in a randomized complete block design with 3 replications. The variety Baltico had the maximum leaf length (19.3 cm), numbers of lateral branches (10.5), internodal length (5.1 cm), flower diameter (8.6 cm), and vase life (24.0 days). The numbers of nodes (5) and flower weight (25.4 g) were highest in the variety Vinco with the lowest cracked area on the stem (0.2 cm2/ crack). The numbers of stem cracks per plant significantly (p ≤0.01) reduced with an increasing level of boron though non-significant relation was observed on 60 ppm and 120 ppm. Variety Baltico was found as a better variety compared to the Vinco, Cervantes and Master varieties according to the vegetative, floral, yield and vase life parameters. Among the levels of boron tested, 60 ppm was found as the optimum dose. Thus, variety Baltico and 60 ppm boron is suggested to be used at the climatic condition of Lalitpur.